Kesalahan berbahasa pada tayangan Fajar Sadboy: percuma cantik kalau bibir SCTV satu untuk semua - Dilla Syahputri; Lisa Septia Dewi br. Ginting (Universitas Asahan, 2023)
This study discusses language errors in the Opra Entertainment Show. The method used to collect data in this study is a qualitative approach with descriptive data analysis. The data used in this research is in the form of verbal data, i.e. podcasts uploaded by Opra Entertainment where it is suspected that there was a language error. The findings of this study indicate that there are several language errors in the Opra Entertainment podcast. The results of the study found that there were language errors in the Opra Entertainment video.